2019
DOI: 10.3390/nu11061294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Native 1,4-Naphthoquinones Plumbagin, Menadione, and Lawsone on Viability, Redox Status, and Mitochondrial Functions of C6 Glioblastoma Cells

Abstract: Background: 1,4-naphthoquinones, especially juglone, are known for their anticancer activity. However, plumbagin, lawsone, and menadione have been less investigated for these properties. Therefore, we aimed to determine the effects of plumbagin, lawsone, and menadione on C6 glioblastoma cell viability, ROS production, and mitochondrial function. Methods: Cell viability was assessed spectrophotometrically using metabolic activity method, and by fluorescent Hoechst/propidium iodide nuclear staining. ROS generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
(41 reference statements)
2
24
1
Order By: Relevance
“…This finding was consistent with that of Khaw et al [ 56 ] who proved that PLB inhibited telomerase in brain tumor cells and resulted in telomere shortening following chronic long-term treatment. Additionally, PLB displayed a highly cytotoxic activity on rat glioblastoma C6 cells (IC 50 = 7.7 ± 0.28 μ M) and caused cell death by necrosis, which was related to the increasing amount of intracellular ROS and significantly uncoupled mitochondrial oxidation from phosphorylation impairing ATP production in cells[ 58 ].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…This finding was consistent with that of Khaw et al [ 56 ] who proved that PLB inhibited telomerase in brain tumor cells and resulted in telomere shortening following chronic long-term treatment. Additionally, PLB displayed a highly cytotoxic activity on rat glioblastoma C6 cells (IC 50 = 7.7 ± 0.28 μ M) and caused cell death by necrosis, which was related to the increasing amount of intracellular ROS and significantly uncoupled mitochondrial oxidation from phosphorylation impairing ATP production in cells[ 58 ].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Superoxide production was found to be higher in OA than N cybrids. Mitochondrial ROS production is directly dependent on mitochondrial function and an increase of this parameter has been linked to the OA pathogenesis [46]. Furthermore, it has also been suggested that mitochondrial dysfunction induces FA oxidation and oxidative stress [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Using in silico molecular docking approach and pharmacological tests, the authors suggested that the active compounds may bind G protein-coupled receptor 55 (GPR55) and exert its pronounced antiproliferative activity against breast cancer cells. 84) Plumbagin (66) and menadione (67) (Fig. 16) were found to be toxic for C6 glioblastoma cells, increased the intracellular ROS amount, significantly uncoupled mitochondrial oxidation from phosphorylation impairing energy productions and caused cell death by necrosis.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%